A case of retroperitoneal venous malformation resected by laparoscopic surgery. Issue 5 (1st June 2022) - Fujinami, Hiroyuki; Kai, Tomoki; Ando, Tadasuke; Shin, Toshitaka; Mimata, Hiromitsu
Abstract : Introduction: Among vascular malformations, venous malformations are the most common type. Among these, retroperitoneal venous malformations are extremely rare. Case presentation: A 60‐year‐old woman was diagnosed with a retroperitoneal tumor 4.5 cm in diameter by abdominal computed tomographic scan. We had difficulty judging whether the tumor was benign or malignant. We performed laparoscopic surgery in order to remove the tumor and make a precise diagnosis. The pathological diagnosis was a venous malformation. Conclusion: Venous malformation located in the retroperitoneum is very rare, and there were few cases that could be removed by laparoscopic surgery. Laparoscopic surgery may be beneficial both for treatment and diagnosis of patients with a small retroperitoneal venous malformation.